BIOCHEMICAL INVESTIGATION ON THE EDIBLE MOLLUSCS OF KERALA II. A STUDY ON THE NUTRITIONAL VALUE OF SOME GASTROPODS AND CEPHALOPODS - SURYANARAYANAN, H; KUMARI, R SHYLAJA; ALEXANDER, K M (Fishery Technology, 2016)
Data on the biochemical composition and food value of the edible portions of two gastropods, Pila virens and Achatina fulica and two cephalopods, Sepiella inermis and Loigo indica have been presented. These molluscs posses nutritive meat very rich in protein and minerals, which compare favourably with popular food fishes in caloric value. The significance of the variations met with in the biochemical constituents of the different species has been di cussed.